Stress in the school counsellor's contemporary role: scale development and validation. Issue 2 (4th March 2023) - Hemi, Alla; Maor, Rotem
ABSTRACT: Given school counsellors' many responsibilities and the misunderstanding of their role by others, it is clear that school counsellors are vulnerable to harmful levels of stress. Existing stress scales provide insufficient solutions for the school counsellor's contemporary role because they are not profession-specific, are unidimensional or outdated. Our purpose was to develop and validate a scale of school counsellors' stress and to examine which stressors are perceived as most stressing. Exploratory factor analysis on a pilot sample (N = 72) revealed eight factors and confirmatory factor analysis on a larger sample (N = 205) yielded a good fit for the eight-factor structure. Participants consistently reported higher levels of stress due to bureaucracy, work-home conflict, teaching and discipline than for misunderstanding and lack of appreciation for the counsellor's role, dealing with violence and conflict resolution. Benefits of measuring specific stressors rather than a unidimensional construct and implications for counsellor training are discussed.